AKTIVITAS METAKOGNISI SISWA KELAS X SMAN 1 TEMBILAHAN DALAM PEMECAHAN MASALAHAN MATEMATIKA DITINJAU DARI GAYA KOGNITIF - Annur, M. Firman; Sujadi, Imam; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aims of this research were to described: (1) the metacognition activities of 10th grade students of Senior High School at 1st Tembilahan with field dependent cognitive style in solving mathematics problem, and (2) the metacognition activities of 10th grade students of Senior High School at 1st Tembilahan with field independent cognitive type in solving mathematics problem.The research was a qualitative descriptive research. The subjects of the research were four 10th grade students of Senior High School at 1st Tembilahan, which consisted of two students with field dependent cognitive style and the rest with field independent cognitive style. The prosedure of selecting the subjects used snowball sampling technique. The data of research was collected through questionnaire and task-based interview technique on subject matter of logarithm. The data were validated using time triangulation. The data were also analyzed using a Miles and Hubermanâs concept, that was data reduction, presentation, and conclusion.The result of this research showed that: (1) the metacognition activities of FIâs students in solving mathematics problem that seems on: (a) plans development activities: writing out all informations that they got quickly, finding out the goal only by viewed important contents of problem, designing a problem solving and imagining itâs steps, and researched the connection between theirs related memory and the problem. (b) performance monitoring activities: correcting theirs own missteps, rethingking of theirs plans and fully convinced with theirs own answer, rechecking over and over theirs answer, finding the different way to solve the problem, analyzing the compatibilities between the answer and the plans that they had. (c) the actions evaluating activities: reobservating to find out the features and lacks of theirs actions, convincing that they capable to solve problem with different ways, evaluating the entire process from beginning until the end. (2) the metacognition activities of FDâs students in solving mathematics problem that seems on: (a) plans development activities: writing out all informations that they got slowly, finding out the goal only by viewed important contents of problem, designing a problem solving and imagining itâs steps, and researched the connection between theirs related memory and the problem. (b) the actions evaluating activities: reobservating of all theirs missteps, and evaluating the entire process from beginning until the end. Futhermore, there was no performance monitoring activities about to find on FDâs students.Keywords: Metacognition Activities, Field Dependent and Field Independent Cognitive Style, Problem SolvingÂ